2016
DOI: 10.1134/s0006297916130034
|View full text |Cite
|
Sign up to set email alerts
|

Structure, properties, and biological relevance of the DNA and RNA G-quadruplexes: Overview 50 years after their discovery

Abstract: G-quadruplexes (G4s), which are known to have important roles in regulation of key biological processes in both normal and pathological cells, are the most actively studied non-canonical structures of nucleic acids. In this review, we summarize the results of studies published in recent years that change significantly scientific views on various aspects of our understanding of quadruplexes. Modern notions on the polymorphism of DNA quadruplexes, on factors affecting thermodynamics and kinetics of G4 folding-un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 430 publications
(679 reference statements)
0
68
0
Order By: Relevance
“…Single-stranded oligos were used in structure characterization of G-quadruplexes for three reasons. First, G-quadruplexes often play a regulatory role in molecular processes where DNA is single-stranded, such as replication, transcription, and repair (Dolinnaya et al 2016). Second, single-strandedness allows better characterization of quadruplex formation and thus is most often used in experimental studies (Dailey et al 2010).…”
Section: Experimental Characterization Of G-quadruplexesmentioning
confidence: 99%
“…Single-stranded oligos were used in structure characterization of G-quadruplexes for three reasons. First, G-quadruplexes often play a regulatory role in molecular processes where DNA is single-stranded, such as replication, transcription, and repair (Dolinnaya et al 2016). Second, single-strandedness allows better characterization of quadruplex formation and thus is most often used in experimental studies (Dailey et al 2010).…”
Section: Experimental Characterization Of G-quadruplexesmentioning
confidence: 99%
“…Our study has shown that besides cellular uptake neutrophil functions can also be modulated by G-quadruplex topology. It should be noted that just telomere G-quadruplexes could adopt a broad range of folding patterns [20,70].…”
Section: Discussionmentioning
confidence: 99%
“…The core of the G-quadruplex consists of two or more stacked planar G-tetrads, in which four guanine bases from different G-tracts interact via Hoogsteen bonding, while the intervening sequences are extruded as loops. DNA and RNA G-quadruplexes are the only non-canonical structures whose presence within genomes was strictly proved [20,21]. Being structural elements of the genome, G-quadruplexes are recognized by numerous proteins and enzymes, whose activity is modulated by these non-canonical DNA structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-stranded oligos were used in structure characterization of G-quadruplexes, for three reasons. First, G-quadruplexes often play a regulatory role in molecular processes where DNA is single-stranded, such as replication, transcription, and repair 72 . Second, single-strandedness allows better characterization of quadruplex formation and thus is most often used in experimental studies 73 .…”
Section: Effect Of Sequence Composition On Ipdsmentioning
confidence: 99%